Telecollaboration as an ELF Environment in the Global Age - Zečević, Snežana M.; Trkulja Milekić, Ljubica M. (Collection of Papers of the Faculty of Philosophy in Priština, 2022)
The focus of this paper is telecollaboration as a remote-learning environment and a way of transcending the distance between two or more groups of learners from different cultures/nations, who use English as a lingua franca (ELF), via computer-mediated-communication (CMC). It is regarded in the light of the qualitative content analysis of numerous theoretical and empirical research, according to which: 1) basic notions concerning ELF and its pedagogical implications, including the issues of culture and identity, are provided; 2) then, telecollaboration in foreign language learning is introduced through a theoretical framework and its general principles; 3) mainstream features of the such virtual educational environment are considered from the global aspect; 4) moreover, the way telecollaboration could be applied for practising the use of ELF is presented, and, finally, 5) its benefits for becoming a competent ELF user are emphasized, as well as possible limitations and suggestions for further researches. Accordingly, the main point of this brief overview is twofold: 1) to promote the possibilities of telecollaboration as a contemporary educational way of virtual information exchange within the ELF paradigm and English language teaching (ELT) field in general, and, 2) to arouse the interest of other researchers in keeping the pace with the similar future educational trends.
Keywords: telecollaboration; English as a lingua franca; intercultural competence; intercultural awareness; language learning; global age